2004
DOI: 10.1248/bpb.27.1414
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Inhibitory Activity of Vietnamese Medicinal Plants

Abstract: Natural products are excellent sources of lead compounds in the search for new medicaments for the treatment of diseases. The largest present underexplored source of such materials lies in tropical and subtropical regions of the world. In these areas, a long tradition of ethnobotanical medicine often exists and offers a rich and relatively untapped source for the discovery of new drugs from natural products. Vietnam, a tropical Southeast Asian country, also has a long history of traditional medicine systems. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(129 citation statements)
references
References 31 publications
6
113
2
4
Order By: Relevance
“…5). The high inhibition effect was comparable with other research related to Iranian medicinal plants [8], Vietnamese traditional medicines [9] and selected Philippine medicinal plants [17]. Therefore, the ethanol extract of herb was obtained to be separated using column chromatography and tested further on their toxicity toward shrimp larvae as well as on their enzymatic activity.…”
Section: The Inhibitory Assay Of Xosupporting
confidence: 76%
See 1 more Smart Citation
“…5). The high inhibition effect was comparable with other research related to Iranian medicinal plants [8], Vietnamese traditional medicines [9] and selected Philippine medicinal plants [17]. Therefore, the ethanol extract of herb was obtained to be separated using column chromatography and tested further on their toxicity toward shrimp larvae as well as on their enzymatic activity.…”
Section: The Inhibitory Assay Of Xosupporting
confidence: 76%
“…The medicinal value of these plants lies in some chemical substances that produce a definite physiological action on the human body. XO inhibitors have been found in a wide variety of plants from Iran [8], and Vietnam [9]. Celery root and leave juices applied alone or with doxorubicin, increased XO activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…XO catalyses the oxidation of xanthine and hypoxanthine into uric acid, which may lead to a disease known as gout (Kong et al, 2000). Some drugs and plant-derived extracts which serve as XO inhibitors may block uric acid biosynthesis, lower the plasma uric acid concentration and are used to treat gout (Nguyen et al, 2004). The tested S. longipedunculata extracts revealed negligible inhibition of AChE, CES and XO.…”
Section: Enzyme Inhibition Activitymentioning
confidence: 99%
“…Many reports showed that the main components in the heartwood of C. sappan are phenolics with anti-inflammatory, antibacterial, and anti-influenza activities (Choi et al, 2007;Cuong et al, 2012;Kim et al, 2012;Namikoshi et al, 1987;Shimokawa et al, 1985;Washiyama et al, 2009). Nguyen et al (2004) reported that the methanolic extract of the heartwood of C. sappan collected in Vietnam exhibited significant XO inhibitory activity. However, limited information is available concerning the principles of the seeds of C. sappan.…”
Section: Introductionmentioning
confidence: 99%